2023
DOI: 10.1039/d2cp04725j
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale computational investigation of Ag-doped two-dimensional Zn-based MOFs for storage and release of small NO and CO bioactive molecules

Abstract: Nitric oxide (NO) and carbon monoxide (CO) are two important gasotransmitters with critical biological roles in the body. Due to their short lifetime and dangerous side effects in high concentrations,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…In the case of CO, from Figure S10, in all types of functional groups, the diffusion of CO molecules is anisotropic. Previous research has confirmed that the diffusion of NO and CO molecules within the (Zn)­MOF-470 structure is anisotropic . Adding functional groups and the directional interactions of guest molecules with these functional groups as well as the change of diffusion space and release of molecules have caused a change in the direction of the movement of NO molecules.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In the case of CO, from Figure S10, in all types of functional groups, the diffusion of CO molecules is anisotropic. Previous research has confirmed that the diffusion of NO and CO molecules within the (Zn)­MOF-470 structure is anisotropic . Adding functional groups and the directional interactions of guest molecules with these functional groups as well as the change of diffusion space and release of molecules have caused a change in the direction of the movement of NO molecules.…”
Section: Resultsmentioning
confidence: 92%
“…70 The geometry optimization of several configurations, as well as the computation of potential energies between NO−NO, CO−CO, CO−H 2 O, NO−H 2 O, and H 2 O−H 2 O, were carried out using the coupled-cluster singles and doubles with perturbative triples method (CCSD(T)) with the aug-cc-pVQZ basis set. To correct for binding energies, all calculations incorporated the basis set superposition error (BSSE) 71 and were performed with a tight optimization condition. Potential energy curves for interactions of NO, CO, and H 2 O are provided in detail in a previous work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, bacteria in the solution of MFCs will propagate on the cathode, contaminating the cathode electrocatalyst and deteriorating the durability of MFCs. 10–12…”
Section: Introductionmentioning
confidence: 99%
“…Besides, bacteria in the solution of MFCs will propagate on the cathode, contaminating the cathode electrocatalyst and deteriorating the durability of MFCs. [10][11][12] To address the high-cost of platinum, non-noble transition metal compounds are considered as promising candidates because of their low-cost and Pt-like electrocatalytic activity. [13][14][15] Among these candidates, Co-based electrocatalysts are most attractive, because they not only present Pt-like electrocatalytic activity towards the ORR but also can prevent the cathode becoming contaminated with bacteria that grow on the cathode and reduce the active cathode sites.…”
Section: Introductionmentioning
confidence: 99%